The Development of Read Riddle Games to Improve Students' Reading Interest - Lira Aulia Hakim; Pahmi Pahmi; Prih Febtiningsih (Universitas Lancang Kuning, 2023)
Reading is an important aspect of the Senior High School curriculum, especially in areas where languages were integrated. The curriculum focuses on teaching grammatical awareness, structure, and reading comprehension to help students progress from basic knowledge to higher levels of language use. This study aims to discover the students’ outcomes by developing learning media using Google Site called